From Ambivalence to Influence: Australia and the Negotiation of the 1968 Nuclear Non-proliferation Treaty - Hubbard, Chris (Blackwell Publishing Asia, 2004)
In early 1967 it appeared that the Eighteen Nation Disarmament Committee in Geneva would successfully negotiate a multilateral treaty to curb global proliferation of nuclear weapons. This triggered an urgent review by the Australian Government of its policies on the civil and military applications of nuclear technology. The need to build a coherent response to a US expectation that its Pacific ally would sign the prospective Nuclear Non-Proliferation Treaty imposed discipline upon a hitherto ad hoc approach to nuclear policy development. Those in the new Gorton Government and the nuclear science bureaucracy who advocated the embrace of nuclear technology—in both its civil and military applications—fought, and ultimately lost, a battle against proponents of the NPT. The resolution of the struggle for supremacy within elements of the policy community impelled the Government to demand and receive concessions from the USA. Originally silent on how the NPT might be interpreted and operationalised in order to maximise support, the US now shared its views with the members of the Western Alliance. US willingness to compromise with Australia in this way exceeded what its Pacific ally had cause to expect and illustrates that middle powers can wield influence on a global scale when circumstances permit.